MYCN Amplified Relapse Following Resolution of MYCN Nonamplified 4S Neuroblastoma With Placental Involvement: A Case Report and Review of the Literature. Issue 5 (July 2019) - Langenberg-Ververgaert, Karin P.S.; Renzi, Samuele; Chung, Catherine T.; Shago, Mary; Lo, Winnie; Davidson, Scott; Villani, Anita; Baruchel, Sylvain; Irwin, Meredith S.; Morgenstern, Daniel A.
Abstract : Congenital neuroblastoma with placental involvement is exceptionally rare, but mortality is high. Detailed examination of placenta including MYCN amplification and segmental chromosomal aberrations should be performed in all suspected cases, as it is noninvasive and readily available. Maternal dissemination has not been reported. In this manuscript, we describe an infant with placental diagnosis of MYCN nonamplified congenital neuroblastoma. This is the first report of a recurrence of congenital 4S neuroblastoma following resolution in which MYCN amplification is only detected in the recurrence. Germline sequencing using a large comprehensive cancer panel did not reveal variants in candidate cancer predisposition genes.